Construction of Phenanthridinone Skeletons through Palladium-Catalyzed Annulation; Journal of Organic Chemistry; Vol. 88, iss. 17 - Xin Geng; Heng He; Shatskiy A. Andrey; Stepanova E. V. Elena Vladimirovna; Alvey G. R. Gregory; Jian-Quan Liu; Karkas M. D. Markus; Xiang-Shan Wang (2023, 2023)
Title screen